Microwave Absorbing Properties of Epoxy-SiO2-Fe3O4 Hybrid Coatings on Plasma Electrolytic Oxidation-Treated Aluminum 6061 - Irma Sianipar; Nur Asriyani; Muhammad Prisla Kamil (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2026)
The escalation of radar detection technology has driven an urgent need for microwave-absorbing materials in stealth technology applications. This study investigates the microwave absorption capabilities of an Epoxy-SiO2-Fe3O4 hybrid composite coating applied to Aluminum 6061 substrates treated with Plasma Electrolytic Oxidation (PEO). The incorporation of 5 g/L malonic acid during the PEO process produced an oxide base layer with a thickness of 5.14 +/- 0.89 um, featuring microporous characteristics that facilitate a mechanical interlocking mechanism for the composite layer. Variations in functional filler compositions (S, F, SF1, SF2, and SF3) were exclusively tested using a Vector Network Analyzer (VNA) across the X-band frequency range (8-12 GHz). The results indicated that all samples exhibited resonance peaks within the 8.7-9.26 GHz range. The most significant absorption was achieved by sample S (100% SiO2) with a Reflection Loss (RL) value of -2.34 dB at 9.26 GHz, followed by sample SF3 (75% SiO2 : 25% Fe3O4) with an RL value of -1.91 dB at 9.02 GHz. This performance demonstrates the dominance of the dielectric loss mechanism at high frequencies, while the addition of Fe3O4 plays a strategic role in modifying magnetic permeability to optimize impedance matching. Although the RL values have not yet reached the technical threshold of -10 dB due to single-coat thickness limitations, the integration of PEO and functional hybrid layers successfully reduced microwave reflection intensity systematically on conductive metal surfaces.